2020
DOI: 10.21203/rs.3.rs-29449/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Oral Protein-Containing Diets Following Elective Lower Gastrointestinal Tract Surgery in Adults: A Meta-Analysis of Randomized Clinical Trials.

Abstract: Background: Although current guidelines make consensus recommendations for the early resumption of oral intake after surgery, a recent comprehensive meta-analysis failed to identify any patient-centred benefits. We hypothesized this finding was attributable to pooling studies providing effective protein-containing diets with ineffective non-protein liquid diets. Therefore, the aim of this paper was to investigate the safety and efficacy of early oral protein-containing diets versus later (traditional) feeding … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This study was conducted and reported in compliance with established methodological guidelines (Moher et al, 2009 ). Detailed study methods were published online in advance of search close-out (Pu et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted and reported in compliance with established methodological guidelines (Moher et al, 2009 ). Detailed study methods were published online in advance of search close-out (Pu et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…(9) In another study anastomosis leakage was seen in 2 (2.02%) cases with early vs 6 (6%) in cases with traditional postoperative feeding. (10) The majority of the studies done in the past are delayed or conventional feeding and it is still being practiced in underdeveloped countries like Pakistan where the data regarding this early feeding is lacking for which this study was planned to collect the local data and look for the better modality in our population.…”
Section: Introductionmentioning
confidence: 99%